Mammospheres of hormonal receptor positive breast cancer diverge to triple-negative phenotype. (April 2018) - Laranjo, Mafalda; Carvalho, Maria João; Costa, Tânia; Alves, André; Oliveira, Rui Caetano; Casalta-Lopes, João; Cordeiro, Patrícia; Botas, Filomena; Abrantes, Ana Margarida; Paiva, Artur; Oliveira, Carlos; Botelho, Maria Filomena
Abstract: Objectives: This study aimed to characterize mammospheres from hormonal receptor (HR) positive and triple-negative breast cancer (TNBC), hypothesizing a differential profile of CSC and differentiation markers, and a stemness enrichment when successive sphere forming-protocols are performed. Methods: Breast cancer cells MCF-7 and HCC1806 were submitted to sphere-forming protocols. The first sphere generation (MS1) was cultured in adherent conditions (G1). This procedure was repeated and generations of mammospheres (MS1, MS2, and MS3) and sphere-derived cells in adherent conditions (G1, G2, and G3) were obtained. The mammosphere forming capacity, self-renewal, area and doubling time were evaluated. Flow cytometry regarding CD133, CD24, and CD44 and western-blot regarding aldehyde dehydrogenase (ALDH), hormonal receptors and P53 expression was performed. Results: Breast cancer cell lines harboured the capacity to form spheres, which originated derived adherent populations. The sphere-forming capacity was enhanced in HCC1806-MS3 compared to MS1. Self-renewal was higher in MCF-7 mammospheres, which also had an increased area. The putative CSC markers CD133 showed tendency to be enhanced in mammospheres but the CD44 + /CD24 -/low phenotype was not identified. The expression of ALDH was greater in mammospheres from MCF-7 and HCC1806 than in the respectively derived adherent cells. The expression of oestrogen receptor (ER)-α, progesterone receptor (PR) and P53 decreased in MCF-7 spheres. ER-β expression was lower in mammospheres from both cell lines compared with parental and derived adherent populations. Conclusions: Loss of HR and P53 expression in HR-positive mammospheres evidences the minor population of CSC which shares characteristics with the TNBC phenotype. Highlights: CSC isolated from HR+ and TNBC present distinct phenotype from parental population. ALDH was corroborated as CSC marker of the mammosphere phenotype. Mammospheres of HR + diverge to TNBC phenotype. HR decrease in CSC isolated from HR + cell line suggests therapeutic implications. P53 and HR absence in CSC suggests a worse response to targeted therapies.